(untitled) (Asian Journal of Medical and Biological Research, 2015)
Physiological status-related changes in serum biochemical values are known to occur in many species. The aim of the current study was to evaluate total serum protein, albumin, glucose, calcium and phosphorus concentration and these parameters were measured by the serum analyzer for lactating (n=50) and non-lactating (n=50) dairy cattle in selected dairy farms of Chittagong district. The results (mean ± standard deviation) of the study showed that among serum biochemical parameters total protein (82.3 ± 2.15 gm/l), albumin (27.45 ± 5.06 gm/l), calcium (12.97±6.67 mg/dl) and phosphorus (7.26 ± 0.41 mg/dl) level in non-lactating cows were higher than the value of lactating cows as (81.28 ± 2.41 gm/l), (14.09 ± 2.05 gm/l), (10.05 ± 2.51 mg/dl) and (6.52 ± 0.30 mg/dl) respectively. Only glucose level in lactating cows (63.01 ± 6.67 mg/dl) was found higher than the non lactating cows (58.47 ± 3.84 mg/dl). In case of parity-wise parameters insignificant variation was noticed. It may be concluded that biochemical variation present between lactating cow and non lactating cow is important for interpretation of laboratory data and also for physiological diagnosis. Asian J. Med. Biol. Res. June 2015, 1(2): 259-264